2005
DOI: 10.1080/15140326.2005.12040621
|View full text |Cite
|
Sign up to set email alerts
|

Government Expenditure and Economic Growth: Evidence from Trivariate Causality Testing

Abstract: This paper seeks to examine if the relative size of government (measured as the share of total expenditure in GNP can be determined to Granger cause the rate of economic growth, or if the rate of economic growth can be determined to Granger cause the relative size of government. For this purpose, we first use a bivariate error correction model within a Granger causality framework, as well as adding unemployment and inflation (separately) as explanatory variables, creating a simple 'trivariate' analysis for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(120 citation statements)
references
References 24 publications
3
114
0
3
Order By: Relevance
“…No-causality in a bivariate system can result from neglected variables (Lütkepohl, 1982). The inclusion of capital and labor in addition to energy incorporates more information that affects economic growth than in the bivariate case where energy alone is considered as the sole factor input (Loizides and Vamvoukas, 2005).…”
Section: Granger Causality Testmentioning
confidence: 99%
See 2 more Smart Citations
“…No-causality in a bivariate system can result from neglected variables (Lütkepohl, 1982). The inclusion of capital and labor in addition to energy incorporates more information that affects economic growth than in the bivariate case where energy alone is considered as the sole factor input (Loizides and Vamvoukas, 2005).…”
Section: Granger Causality Testmentioning
confidence: 99%
“…Thus the previous bivariate causality tests between energy consumption and economic growth may be invalid due to the omission of important variables affecting both energy consumption and economic growth. It is possible that the introduction of capital and labor in the causality framework may not only alter the direction of causality but also the magnitude of the estimates (Loizides and Vamvoukas, 2005;Odhiambo, 2008). Further, since a four VAR case incorporates more information than the bivariate case, the causal inference drawn can be more reliable (Loizides and Vamvoukas, 2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lütkepohl [9] indicated that omitted of relevant variables in the estimation contributes to bias and inconsistent results. Inclusion of control variables such as capital and labor in a multivariate model helps to provide more reliable result (Loizides and Vamvoukas [10]). …”
Section: Introductionmentioning
confidence: 98%
“…In the same context,Loizides and Vamvoukas (2005) stress that considering third or fourth variable in…”
mentioning
confidence: 96%